Intratumoral in-situ cross-linking hydrogel nano-composite as well as preparation method and application thereof

By designing a hydrogel nanocomplex composed of manganese dioxide, lactate oxidase and hyaluronic acid, the problem of regulating acidic and hypoxic properties in the tumor microenvironment is solved, and the M1 polarization and radioimmunotherapy effect of tumor-associated macrophages are improved.

CN119745786AActive Publication Date: 2025-04-04SUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411907910.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The acidic and hypoxic properties in the tumor microenvironment lead to reduced radiation resistance and immunotherapy effects, and the prior art is difficult to effectively regulate these conditions.

Method used

Design a hydrogel nanocomplex targeting the tumor microenvironment, and form a complex composed of manganese dioxide, lactate oxidase and hyaluronic acid through specific preparation methods, which can play a synergistic role in the tumor microenvironment, regulate acidic and hypoxic conditions, and promote the polarization of tumor-associated macrophages to M1.

Benefits of technology

Effectively improve low pH and low oxygen conditions in the tumor microenvironment, promote the polarization of tumor-associated macrophages to M1, improve the effect of radioimmunotherapy, and promote the apoptosis of tumor cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119745786A_ABST
    Figure CN119745786A_ABST
Patent Text Reader

Abstract

The invention discloses an intratumoral in-situ cross-linked hydrogel nano-composite and a preparation method and application thereof, and the method comprises the following steps: dropwise adding MAA into an HA solution while stirring at a high speed, then stirring at a high speed at 0 DEG C for a period of time, dialyzing with a dialysis bag, and freeze-drying to obtain HAMA; adding the potassium permanganate solution into the HAMA solution, mixing, dialyzing by using a dialysis bag, and freeze-drying to obtain a HAMA-MnO2 composite material; and dissolving the HAMA-MnO2 composite material in ultrapure water, adding lactate oxidase, and mixing to obtain the intra-tumor in-situ cross-linking hydrogel nano-composite. According to the intratumor in-situ cross-linked hydrogel nano-composite, hydrogel can be formed in the local part of a tumor through the cross-linking reaction of hyaluronic acid and calcium ions, the local slow-release effect of a medicine is achieved, meanwhile, the synergistic effect of manganese dioxide and lactate oxidase is combined, the tumor microenvironment can be effectively adjusted, and the tumor healing effect is improved. Therefore, the effect of radioimmunotherapy is improved, and apoptosis of tumor cells is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogel nanocomposite materials, and specifically relates to an intratumoral in situ cross-linked hydrogel nanocomposite that targets the acidity and hypoxia dual regulation of the tumor microenvironment, and a preparation method and application thereof. Background Art

[0002] The tumor microenvironment (TME) is a complex ecosystem, and its historical concept originated from the relationship between inflammation and cancer proposed by Virchow in the 19th century and Paget's "seed and soil" theory. The tumor microenvironment is shaped by the activities of cancer cells and contains a variety of cell types, extracellular matrix, vascular networks and immune cells, which together affect tumor growth, invasion and response to treatment. In particular, immune cells in the tumor microenvironment, such as tumor-associated macrophages (TAMs), play a key role in tumor immune escape and immunotherapy resistance.

[0003] Tumor-associated macrophages contribute to tumor immune escape and treatment resistance by secreting immunosuppressive factors and promoting angiogenesis, while M1 macrophages have anti-tumor activity. Radiotherapy and immunotherapy are the two mainstays of tumor treatment, but their effectiveness is often affected by TME. The acidic and hypoxic properties of TME can lead to radiotherapy resistance, because hypoxic cells are insensitive to radiation, while the acidic environment may inhibit the activity of immune cells and reduce the effectiveness of immunotherapy. Therefore, regulatory strategies targeting the tumor microenvironment, such as improving hypoxia and acidity and promoting the polarization of tumor-associated macrophages to M1, have become an important research direction to improve the effectiveness of radiotherapy and immunotherapy.

[0004] In the field of tumor microenvironment regulation and enhanced immunotherapy, researchers are exploring a variety of strategies to enhance the immune system's ability to kill tumors. These strategies aim to improve the tumor microenvironment, making it more conducive to the activity and proliferation of immune cells, thereby improving the effectiveness of immunotherapy. These strategies include macrophage polarization regulation, inhibition of tumor-associated macrophage recruitment, and tumor-associated macrophage exhaustion. As a new type of biomaterial, hydrogels have also shown their unique advantages and application prospects in regulating tumor-associated macrophages and improving the tumor microenvironment. Currently published studies on hydrogel composites that improve the tumor microenvironment can be roughly divided into the following types:

[0005] (1) Thermosensitive hydrogel material composites, such as the Gel / (REG+NG / LY) hydrogel system reported by Li et al. that can be used to amplify immune activation, and the LPR@CHG nanoparticle composite that can reprogram the tumor immune niche reported by Gao et al.;

[0006] (2) Ion-crosslinked hydrogel material composites, such as Shen et al. developed a sodium alginate hydrogel composed of elesclomol-Cu and galactose, which can form a gel with physiological concentrations of calcium ions, and Ding et al. reported a tumor microenvironment and near-infrared (NIR) light dual-responsive prodrug hydrogel APPF for synergistic immunotherapy of cancer;

[0007] (3) Postoperative implantation of hydrogel material complexes, such as PSBMA hydrogel-encapsulated doxorubicin Gel@M / CuO, which is used for adjuvant treatment after breast cancer surgery, and hyaluronic acid hydrogel-encapsulated CAR-T, which helps enhance the distribution of CAR-T cells in the surgical bed.

[0008] In summary, the hydrogel nanosystem has significant advantages in the treatment of tumor microenvironment, provides new strategies and methods for cancer treatment, and indicates that its application prospects in the biomedical field are broader.

[0009] Hyaluronic acid is a water-soluble natural polysaccharide that can react with multivalent cations (such as Ca 2+ ) cross-linked, at physiological concentrations of Ca 2+ Hydrogels are formed rapidly under the condition of being exposed to water. Hydrogels composed of cross-linked polymer networks are often used for local controlled release of therapeutic drugs. Hydrogels can be used as efficient drug carriers to load chemotherapeutic drugs, biologics or other therapeutic agents, which can act directly on the tumor microenvironment through local injection or implantation. This mode of administration can increase the concentration of drugs at the tumor site while reducing systemic side effects. Recently, various hydrogel-based nanocomposites have attracted attention and have been designed for tumor treatment. Hyaluronic acid has excellent biocompatibility and can be degraded in the body, reducing long-term effects on the human body. In addition, the softness and plasticity of nanohydrogels enable them to better integrate with tumor tissues and improve therapeutic effects.

[0010] These hydrogel drug delivery systems not only have the functions of each component, but also have synergistic effects. Among them, there are many basic research applications on materials that relieve hypoxia and low pH in the tumor microenvironment. Hypoxia and low pH are key characteristics of the tumor microenvironment, which have a significant impact on tumor growth, invasion, metastasis and treatment response. Hypoxia and low pH environments inhibit the function of immune cells, promote the aggregation of immunosuppressive cells, and help tumor immune escape. In addition, these conditions increase the resistance of tumor cells to radiotherapy and certain chemotherapy drugs, and affect the distribution and activity of drugs. Therefore, increasing oxygen concentration or adjusting pH is a potential strategy for treating tumors by improving the tumor microenvironment. Summary of the invention

[0011] In view of the problems existing in the prior art, the present invention provides an intratumoral in situ cross-linked hydrogel nanocomposite that targets the acidity and hypoxia of the tumor microenvironment and dual regulation, and a preparation method and application thereof. The hydrogel nanocomposite is formed by manganese dioxide, lactate oxidase and hyaluronic acid through a specific preparation method, and can play a synergistic role in the tumor microenvironment, regulate the tumor microenvironment, improve low pH and hypoxic conditions, and promote the polarization of tumor-associated macrophages to M1, thereby helping to improve the effect of radioimmunotherapy.

[0012] In order to solve the above technical problems, the present invention is implemented through the following technical solutions:

[0013] A method for preparing an intratumoral in situ cross-linked hydrogel nanocomposite comprises the following steps:

[0014] Step 1, completely dissolving hyaluronic acid (HA) in ultrapure water, adding methacrylic anhydride (MAA) dropwise while stirring at high speed, and then stirring at high speed for a period of time at 0°C;

[0015] Step 2, dialyzing the solution obtained in step 1 for a period of time using a dialysis bag with a specific molecular weight cut-off, and freeze-drying to obtain methacrylated hyaluronic acid (HAMA);

[0016] Step 3: Dissolve the methacrylated hyaluronic acid (HAMA) obtained in step 2 in ultrapure water, and then add potassium permanganate solution (KMnO 4 ) mixed and stirred, and potassium permanganate was reduced to manganese dioxide by utilizing the energy of double bonds;

[0017] Step 4: The mixed solution obtained in step 3 is dialyzed for a period of time using a dialysis bag with a specific molecular weight cut-off, and then freeze-dried to obtain a methacrylated hyaluronic acid-manganese dioxide composite material (HAMA-MnO 2 );

[0018] Step 5: The methacrylated hyaluronic acid-manganese dioxide composite material (HAMA-MnO 2 ) was dissolved in ultrapure water, lactate oxidase (LOX) was added, and the mixture was stirred thoroughly to obtain an intratumoral in situ cross-linked hydrogel nanocomposite, namely HAMA-MnO 2 / LOX;

[0019] The HAMA-MnO 2 / LOX can react with physiological concentrations of Ca 2+ Solution cross-linking generates MnO 2 Nanoparticles and LOX hydrogels.

[0020] Furthermore, in step 1, the high-speed stirring time is 24 hours.

[0021] Furthermore, in step 2, the molecular weight cutoff of the dialysis bag is 8000-14000 kDa, and the dialysis time is 48 hours.

[0022] Further, in step 3, when potassium permanganate solution (KMnO 4 ) changes from purple to brown, indicating that the potassium permanganate in the mixed solution has been completely reduced to manganese dioxide.

[0023] Furthermore, in step 4, the molecular weight cutoff of the dialysis bag is 3000 kDa, and the dialysis time is 48 h.

[0024] An intratumor in-situ cross-linked hydrogel nanocomposite is prepared by adopting the above-mentioned method for preparing the intratumor in-situ cross-linked hydrogel nanocomposite.

[0025] A novel application of the above-mentioned intratumoral in situ cross-linked hydrogel nanocomplex for synergistically regulating the immune response and the polarization state of tumor-associated macrophages in the tumor microenvironment.

[0026] Furthermore, it is especially used to synergistically improve the low pH and hypoxia conditions in the tumor microenvironment, and promote the polarization of tumor-associated macrophages to M1, thereby increasing or decreasing the effect of radioimmunotherapy.

[0027] A new application of the above intratumoral in situ cross-linked hydrogel nanocomposite is used as a drug delivery system or drug loading system for anticancer drugs including chemotherapeutic drugs and biological agents.

[0028] Furthermore, the drug delivery system or drug loading system of the anticancer drug can form a MnO-containing 2 Nanoparticles and LOX hydrogels play a synergistic role in the tumor microenvironment, improving low pH and hypoxic conditions, promoting the polarization of tumor-associated macrophages to M1, thereby helping to improve the effect of radioimmunotherapy and promoting the apoptosis of tumor cells.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The intratumoral in situ cross-linked hydrogel nanocomposite (particles) of the present invention is prepared from manganese dioxide, lactate oxidase and hyaluronic acid by a specific preparation method. The preparation process is relatively simple and easy to mass produce, thereby reducing production costs.

[0031] 2. The intratumoral in situ cross-linked hydrogel nanocomposite (particles) of the present invention can form hydrogel locally in the tumor through the cross-linking reaction of hyaluronic acid and calcium ions, thereby achieving a local sustained release effect of the drug and improving the targeting and therapeutic effect of the drug.

[0032] 3. The intratumoral in situ cross-linked hydrogel nanocomplex (particles) of the present invention combines the synergistic effects of manganese dioxide, lactate oxidase and hyaluronic acid, and can effectively regulate the immune response in the tumor microenvironment and the polarization state of tumor-associated macrophages, especially effectively improve the low pH and hypoxia problems of the tumor microenvironment, promote the polarization of tumor-associated macrophages to M1, thereby improving the effect of radioimmunotherapy and promoting the apoptosis of tumor cells.

[0033] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0035] Figure 1 HAMA-MnO prepared in Example 1 of the present invention 2 Figure 2. Results of characterization of basic properties of nanocomposites.

[0036] Figure 2 HAMA-MnO obtained in Example 2 of the present invention 2 / Ca 2+ Figure 3. Gel structure characterization results of hydrogel.

[0037] Figure 3 HAMA-MnO in Example 3 of the present invention 2 Figure 3. Test results of the degradation of lactic acid and the repolarization of tumor-associated macrophages by the / LOX composite material.

[0038] Figure 4 HAMA-MnO in Example 4 of the present invention 2 Figure 3. Test results of the hypoxia-regulating effect of / LOX composite material on tumor microenvironment.

[0039] Figure 5 HAMA-MnO in Example 5 of the present invention 2 Figure 3. Test results of the effect of / LOX composite materials on the function of immune cells in the tumor microenvironment.

[0040] Figure 6 HAMA-MnO prepared by the present invention 2 / LOX composites and physiological concentrations of Ca 2+ Solution cross-linking generates MnO 2Schematic diagram of the reaction between nanoparticles and LOX hydrogel. DETAILED DESCRIPTION

[0041] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings so that the purpose, features and advantages of the invention can be more clearly understood. It should be understood that the embodiments shown in the accompanying drawings are not intended to limit the scope of the present invention, but are only intended to illustrate the essential spirit of the technical solution of the present invention.

[0042] In the following description, certain specific details are set forth for the purpose of illustrating various disclosed embodiments to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the relevant art will recognize that the embodiments may be practiced without one or more of these specific details. In other cases, well-known devices, structures, and techniques associated with the present application may not be shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.

[0043] Unless the context requires otherwise, throughout the specification and claims, the word "comprise" and variations such as "include" and "have" should be construed in an open, inclusive sense, ie, should be interpreted as "including, but not limited to."

[0044] References throughout the specification to "one embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout the specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any manner in one or more embodiments.

[0045] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. It should be noted that the term "or" is generally employed in its sense including "and / or" unless the context clearly dictates otherwise.

[0046] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.

[0047] In the field of tumor treatment, the acidic and hypoxic properties of the tumor microenvironment have always been a hot topic of research. These properties not only promote tumor invasion and metastasis, but also lead to immunosuppression and radiotherapy resistance of tumor-associated macrophages, which seriously hinder the therapeutic effect. Tumor-associated macrophages play a complex role in the tumor microenvironment, and their polarization state has a significant impact on tumor progression and treatment response. The present invention designs an intratumoral in situ cross-linked hydrogel complex. This strategy aims to reverse the hypoxic and acidic microenvironment of the tumor, thereby promoting the polarization of tumor-associated macrophages to M1 type. The implementation of this strategy is expected to significantly improve the efficacy of combined radioimmunotherapy and bring new breakthroughs to tumor treatment.

[0048] Example 1

[0049] HAMA-MnO 2 Synthesis of composite materials:

[0050] First, completely dissolve hyaluronic acid HA in ultrapure water to obtain HA solution (10 mg / mL, 200 mL). Then, while stirring at high speed, add methacrylic anhydride MAA (1.035 g / m, 5 mL) dropwise to the HA solution (10 mg / mL, 200 mL), and stir at high speed at 0 ° C for 24 hours. Subsequently, dialyze for 48 hours with a dialysis bag with a molecular weight cutoff of 8000-14000 kDa, freeze-dry to obtain methacrylated hyaluronic acid powder HAMA, and store it for later use. Next, dissolve the HAMA powder in ultrapure water to obtain a HAMA solution (10 mg / mL, 50 mL), and then add potassium permanganate solution KMnO 4 (1.05 mg / mL, 1 mL) was mixed and stirred, and potassium permanganate was reduced to manganese dioxide using the energy of the double bond. 4 When the color of the solution changes from purple to brown, it indicates that potassium permanganate has been completely reduced to manganese dioxide. Finally, the mixed solution is dialyzed for 48 hours using a dialysis bag with a molecular weight cutoff of 3000 kDa, and freeze-dried to obtain a methacrylated hyaluronic acid-manganese dioxide composite material, namely HAMA-MnO 2 Nanocomposites.

[0051] See also Figure 1 As shown, Figure 1 HAMA-MnO prepared in this example 2 The basic properties of the nanocomposite are characterized in Figure 2. 2 Nanocomposite, in this embodiment, methacrylated hyaluronic acid (HAMA) was first synthesized. Figure 1The hydrogen spectrum of A shows that the active hydrogen of carboxylic acid, hydroxyl and amino groups on HAMA disappears, and the 32nd olefinic hydrogen on HAMA exists (around 6.28ppm), and the 4th alkyl hydrogen affected by two oxygens is located around 5.8ppm. The alkyl singlets on HAMA are all in the high field, and the remaining alkyl hydrogens are split between 3.45ppm and 4ppm. Figure 1 As shown in the infrared spectrum of B, it can be seen from the infrared spectrum of HAMA that 3302cm -1 The peak at 1655 cm is the stretching vibration absorption peak of NH and OH in HA. -1 The peak at 1381 cm is the stretching vibration absorption peak of the C=C double bond in methacrylic acid. -1 The bending vibration absorption peak of -CH3 in methacrylic acid is located at 2 After HAMA and MnO 2 The generated hydrogen bonding force leads to an increase in the intensity of the absorption peak.

[0052] Example 2

[0053] HAMA-MnO 2 Composite gelation and hydrogel related characterization:

[0054] Measurement of HAMA-MnO 2 The intratumoral gelation performance of the composite material was studied by mixing different concentrations of HAMA-MnO obtained in Example 1 with 2 Composite materials (0, 1, 5, 10, 20 mg / mL, 2 mL) and physiological concentrations of Ca 2+ The solution (1.8mmoL / , 1mL) was mixed and allowed to stand for 5 minutes. When the concentration reached 10mg / mL, HAMA-MnO 2 With Ca 2+ Cross-linking occurs to form a hydrogel. The reaction principle is as follows Figure 6 Then HAMA-MnO 2 / Ca 2+ Place in a large amount of water to swell for 24 hours and freeze-dry. The freeze-dried gel is fractured by liquid nitrogen and photographed using a scanning electron microscope to observe the swelling pores and drug loading of the hydrogel. 2 (10 mg / mL, 50 mL) and FITC-NH 2 (1.018 mg / mL, 1 mL) was stirred in the dark for 2 h, then dialyzed in a dialysis bag with a molecular weight cutoff of 3000 kDa for 24 h in the dark, and then freeze-dried and fully dissolved in ultrapure water. 2(10.4 mg / mL, 50 μL) was injected into the subcutaneous tumor of mice. After 24 hours, the tumor was sliced ​​and the gel formation in the tumor was observed under a fluorescence microscope.

[0055] See also Figure 2 As shown, Figure 2 The HAMA-MnO obtained in this example 2 / Ca 2+ The hydrogel structure characterization results are shown in Figure 2. Figure 2 The appearance photo of B shows that HAMA-MnO 2 Capable of reacting with physiological concentrations of Ca 2+ The solution is cross-linked to form a hydrogel. Figure 2 The scanning electron microscope image of A shows that in HAMA-MnO 2 / Ca 2+ The scanning electron microscope image shows uniform pores. 2 / Ca 2+ In the SEM image, MnO with a size of about 40 nm can be found. 2 Nanoparticles. In addition, Figure 2 As shown in C, PBS was used as a control, HAMA and HAMA-MnO 2 Both formed porous gel structures in the tumor and stayed in the tumor for more than 24 hours.

[0056] Example 3

[0057] HAMA-MnO 2 Degradation of lactic acid and repolarization of tumor-associated macrophages by / LOX composite materials:

[0058] Establishment of co-culture model of tumor-associated macrophages and tumor cells: The two cells were co-cultured using Transwell chambers. They were divided into five groups, and the lower layer was plated with BMDM of the same concentration (2*10 6 pcs / well), and different concentrations of CT26 (0 pcs / well, 3.8*10 5 Pieces / hole, 1.12*10 6 / hole, 1.86*10 6 / well) and IL-4 (40ng / mL) positive control were plated. After co-culture for 24h after iron wall, the supernatant was taken to detect the lactate concentration by UV-visible spectrophotometer, and the lower layer BMDM was collected to detect the polarization of macrophages by flow cytometry, and the group with the best polarization was screened for repolarization experiment.

[0059] Detection of HAMA-MnO 2 / LOX's ability to repolarize macrophages: Remove the upper layer of CT26 cells and take HAMA, HAMA-MnO 2 , HAMA / LOX, HAMA-MnO 2 The lyophilized powder of / LOX was added to the upper layer, and LPS was used as a positive control and co-cultured with BMDM for 24 hours. The supernatant was then taken for detection of lactate concentration using a UV-visible spectrophotometer, and the lower layer of BMDM was collected for flow cytometry to detect the repolarization effect of the composite material. + Prove that macrophages are polarized to M1 type, CD206 + This demonstrates that macrophages are polarized toward the M2 type.

[0060] See also Figure 3 As shown, Figure 3 HAMA-MnO 2 The test results of the degradation of lactic acid and the repolarization of tumor-associated macrophages by the / LOX composite material. Figure 3 As shown in A, HAMA-MnO 2 It showed good biocompatibility in 3T3, BMDM and CT26, and 200 μg / mL was used in subsequent experiments. We then tested the lactate concentration in the cell culture supernatant, such as Figure 3 As shown in B, as the concentration of tumor cells increases, the concentration of lactate also increases. Figure 3 As shown in Figure C, after using the composite material, it was found that the composite material containing LOX had a significantly better degradation effect on lactic acid than the group without LOX. Figure 3 As shown in D, as the concentration of CT26 increases, the proportion of BMDM polarized toward M2 increases. Figure 3 As shown in E, HAMA-MnO 2 The M2 ratio of the / LOX composite material group was the lowest, which indicates that this group has the best repolarization effect on tumor-associated macrophages.

[0061] Example 4

[0062] HAMA-MnO 2 Hypoxia-regulating effect of / LOX composite materials on tumor microenvironment:

[0063] [Ru(dpp) 3 ]Cl 2 Oxygen probe detection HAMA-MnO 2 / LOX composite material on the regulation of tumor microenvironment: At the end of the treatment cycle of mice, [Ru(dpp) 3 ]Cl 2The oxygen probe (15 mg / L, 20 μL) was injected into the subcutaneous tumor (CT26) of mice and observed with a confocal microscope 24 hours later. The stronger the green fluorescence signal, the higher the oxygen content in the tumor. The animal experiment was divided into 7 groups: blank control group, radiotherapy group, radiotherapy plus HAMA group, radiotherapy plus HAMA-MnO group 2 group, radiotherapy plus HAMA / LOX group, radiotherapy plus MnO 2 / LOX group, radiotherapy plus HAMA-MnO 2 / LOX group.

[0064] See also Figure 4 As shown, Figure 4 HAMA-MnO 2 / LOX composite material on the hypoxia regulation of tumor microenvironment test results. The results show that the MnO 2 The intensity of green fluorescence in the treated group was much stronger than that in the group without MnO 2 The treatment group and the control group showed that the 2 The treatment group had a better regulatory effect on the hypoxic characteristics of the tumor microenvironment.

[0065] Example 5

[0066] HAMA-MnO 2 / LOX composite material sensitizing effect on radiotherapy:

[0067] HAMA-MnO 2 / LOX composite material sensitization effect on radiotherapy: The animal experiment was divided into 7 groups, namely blank control group, radiotherapy group, radiotherapy plus HAMA group, radiotherapy plus HAMA-MnO 2 group, radiotherapy plus HAMA / LOX group, radiotherapy plus MnO 2 / LOX group, radiotherapy plus HAMA-MnO 2 / LOX group. TUNEL staining was used to examine the survival of tumor cells. The more obvious the apoptosis, the stronger the green fluorescence expression. At the same time, the size of the mouse tumor was recorded.

[0068] HAMA-MnO 2 / LOX composite material on the immune regulation of tumor microenvironment: After the treatment cycle, tumor tissue was taken and flow cytometry was used to detect the polarization expression of tumor-associated macrophages, CD86 + Prove that macrophages are polarized to M1 type, CD206 + The results showed that macrophages were polarized to M2 type. The levels of other key cytokines such as IFN-γ, TGF-β, IL-10 in the venous blood of mice were measured by ELISA method, and the HAMA-MnO 2Effects of / LOX composites on the function of immune cells in the tumor microenvironment.

[0069] See also Figure 5 As shown, Figure 5 HAMA-MnO 2 The test results of the effect of / LOX composite materials on the function of immune cells in the tumor microenvironment. Figure 5 A shows that in the subcutaneous tumors of mice, the apoptosis of the tumors in the treatment group containing LOX is more obvious than that in other treatment groups and the control group, which indicates that the regulation of lactate has a direct or indirect inhibitory effect on the tumor. 2 Compared with before LOX, the blank control group, radiotherapy group, and radiotherapy plus HAMA group did not show obvious TUNEL fluorescence. Figure 5 As shown in B, the double positive fluorescence intensity of CD206 and F480 showed a decreasing trend. The expression of M2 macrophages in tumor tissues of the blank control group was the highest, and the expression of M2 macrophages in tumor tissues of the blank control group was the highest. 2 The expression of M2 macrophages in the / LOX group was the lowest, and there was no significant change in M2 macrophages in the radiotherapy group. Figure 5 As shown in C, the change of tumor volume showed a decreasing trend, in which radiotherapy plus HAMA-MnO 2 The tumor proliferation in the / LOX group was the slowest. Figure 5 D. Figure 5 As shown in E, the concentration of IFN-γ showed a decreasing trend, while the concentration of IL-10 showed an increasing trend. 2 / LOX composite material has good radiosensitization and tumor-associated macrophage repolarization effects.

[0070] In summary, HAMA-MnO 2 The / LOX composite significantly enhanced the efficacy of radiotherapy and promoted the apoptosis of tumor cells by regulating the immune response and macrophage polarization state in the tumor microenvironment. The application of this composite material not only improves the therapeutic effect, but also may provide a new strategy for tumor immunotherapy. Future studies will further explore its potential for application in clinical treatment, in order to bring more effective treatment options to cancer patients.

[0071] It can be seen that the HAMA-MnO prepared by the present invention 2 The / LOX composite material is actually an intratumoral in situ cross-linked hydrogel nanocomposite that targets the acidity and hypoxia of the tumor microenvironment. It can assist in the treatment of cancer and is used to synergistically regulate the immune response and polarization state of tumor-associated macrophages in the tumor microenvironment, especially to synergistically improve the low pH and hypoxia conditions in the tumor microenvironment, promote the polarization of tumor-associated macrophages to M1, and increase or decrease the effect of radioimmunotherapy.

[0072] Furthermore, the HAMA-MnO prepared by the present invention 2 The HA / LOX composite material is expected to be used as a drug delivery system or drug carrier system for anticancer drugs (chemotherapeutic drugs, biological agents or other drugs). The drug delivery system or drug carrier system for anticancer drugs can form MnO-containing cross-linked structures in the tumor through the cross-linking reaction between its own hyaluronic acid and calcium ions. 2 Nanoparticles and LOX hydrogels play a synergistic role in the tumor microenvironment, improving low pH and hypoxic conditions, promoting the polarization of tumor-associated macrophages to M1, thereby helping to improve the effect of radioimmunotherapy and promoting the apoptosis of tumor cells.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an intratumoral in situ cross-linked hydrogel nanocomposite, characterized in that: The following steps are involved: Step 1, completely dissolve hyaluronic acid in ultrapure water, add methacrylic anhydride dropwise while stirring at high speed, and then stir at high speed for a period of time at 0°C; Step 2, dialyzing the solution obtained in step 1 for a period of time using a dialysis bag with a specific molecular weight cut-off, and freeze-drying to obtain methacrylated hyaluronic acid; Step 3, dissolving the methacrylated hyaluronic acid obtained in step 2 in ultrapure water, then adding potassium permanganate solution and mixing and stirring, and reducing potassium permanganate to manganese dioxide by utilizing the energy of double bonds; Step 4, dialyzing the mixed solution obtained in step 3 for a period of time using a dialysis bag with a specific molecular weight cut-off, and freeze-drying to obtain a methacrylated hyaluronic acid-manganese dioxide composite material; Step 5, dissolving the methacrylated hyaluronic acid-manganese dioxide composite material obtained in step 4 in ultrapure water, adding lactate oxidase, and stirring thoroughly to obtain an intratumoral in situ cross-linked hydrogel nanocomposite, namely, HAMA-MnO2 / LOX; The HAMA-MnO2 / LOX can react with physiological concentrations of Ca 2+ Solution cross-linking generated hydrogels with manganese dioxide nanoparticles and lactate oxidase.

2. The method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite according to claim 1, characterized in that: In step 1, the high-speed stirring time is 24 hours.

3. The method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite according to claim 1, characterized in that: In step 2, the molecular weight cutoff of the dialysis bag is 8000-14000 kDa, and the dialysis time is 48 h.

4. The method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite according to claim 1, characterized in that: In step 3, when the color of the potassium permanganate solution changes from purple to brown, it means that the potassium permanganate in the mixed solution has been completely reduced to manganese dioxide.

5. The method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite according to claim 1, characterized in that: In step 4, the molecular weight cutoff of the dialysis bag is 3000 kDa, and the dialysis time is 48 h.

6. An intratumoral in situ cross-linked hydrogel nanocomposite, characterized in that: The method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite is used as described in any one of claims 1 to 5.

7. An intratumoral in situ cross-linked hydrogel nanocomposite prepared by the method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite according to any one of claims 1 to 5 or a use of the intratumoral in situ cross-linked hydrogel nanocomposite according to claim 6, characterized in that: Used to synergistically regulate the immune response in the tumor microenvironment and the polarization state of tumor-associated macrophages.

8. The use according to claim 7, characterized in that: In particular, it is used to synergistically improve the low pH and hypoxic conditions in the tumor microenvironment and promote the polarization of tumor-associated macrophages to M1.

9. An intratumoral in situ cross-linked hydrogel nanocomposite prepared by the method for preparing the intratumoral in situ cross-linked hydrogel nanocomposite according to any one of claims 1 to 5 or a use of the intratumoral in situ cross-linked hydrogel nanocomposite according to claim 6, characterized in that: Used as a drug delivery system or drug carrier system for anti-cancer drugs including chemotherapy drugs and biological agents.

10. The use according to claim 9, characterized in that: The drug delivery system or drug loading system of the anticancer drug can form a hydrogel with manganese dioxide nanoparticles and lactate oxidase in the tumor through the cross-linking reaction of its own hyaluronic acid and calcium ions, and play a synergistic role in the tumor microenvironment, improve low pH and hypoxia conditions, and promote tumor-associated macrophages to polarize to M1, thereby helping to improve the effect of radioimmunotherapy and promote the apoptosis of tumor cells.

Citation Information

Patent Citations

  • Responsive hyaluronic acid fluorescent nanogel, preparation method and application

    CN111588690A

  • Preparation method and anti-tumor application of manganese dioxide nanosheet hybrid hydrogel

    CN111671899A

  • Manganese-based composite hydrogel as well as preparation method and application thereof

    CN116725942A

  • Manganese-based nanogel, medicine taking nanogel as carrier and anti-sugar, antibacterial and anti-tumor application

    CN118286166A